2020
DOI: 10.2147/cmar.s268871
|View full text |Cite
|
Sign up to set email alerts
|

<p>microRNA-139-3p Inhibits Malignant Behaviors of Laryngeal Cancer Cells via the KDM5B/SOX2 Axis and the Wnt/β-Catenin Pathway</p>

Abstract: Background: Laryngeal cancer (LCA) is a common head and neck cancer. Lysine demethylase 5B (KDM5B) knockdown is expected as a new target for cancer prevention. We investigated the molecular mechanism of KDM5B in LCA. Materials and Methods: The levels of KDM5B, microRNA (miR)-139-3p and highmobility-group box 2 (SOX2) in LCA tissues and cells, normal tissues and cells were detected. The effect of KDM5B on LCA was evaluated. The upstream miR of KDM5B and the downstream gene and pathway of KDM5B were predicted an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Hsa-miR-139-3p has been con rmed to be down regulated in LSCC [26,27], which inhibits LSCC development by targeting rab5a [28], KDM5B/SOX2 axis and Wnt/β-catenin pathway [29]. Based on the above data and our ndings, we have reason to believe that hsa-miR-139-3p can be used as a reliable marker for the diagnosis and prognosis of LSCC.…”
Section: Discussionsupporting
confidence: 54%
“…Hsa-miR-139-3p has been con rmed to be down regulated in LSCC [26,27], which inhibits LSCC development by targeting rab5a [28], KDM5B/SOX2 axis and Wnt/β-catenin pathway [29]. Based on the above data and our ndings, we have reason to believe that hsa-miR-139-3p can be used as a reliable marker for the diagnosis and prognosis of LSCC.…”
Section: Discussionsupporting
confidence: 54%
“…In contrast to miR-139-5p , few studies have evaluated the importance of miR-139-3p in cancer because it is a passenger strand. Recently, it was reported that miR-139-3p directly regulates KDM5B (lysine demethylase 5B), a key regulator of histone 3 lysine 4 demethylation in laryngeal squamous cell carcinoma [ 28 ]. Ectopic expression of miR-139-3p suppressed cancer cell malignant behavior by inhibiting the Wnt/β-catenin pathway [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that miR-139-3p directly regulates KDM5B (lysine demethylase 5B), a key regulator of histone 3 lysine 4 demethylation in laryngeal squamous cell carcinoma [ 28 ]. Ectopic expression of miR-139-3p suppressed cancer cell malignant behavior by inhibiting the Wnt/β-catenin pathway [ 28 ]. In the HeLa cervical cancer cell line, miR-139-3p was reduced upon increasing expression of circular RNA hsa_circ_0031288 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of those, 166 were excluded for describing HNSCC cases without focus on the larynx ( n = 28), for being exclusively in vitro studies ( n = 39), for having a number of patients less than 10 or for using patient data from public databases ( n = 50), for not quantifying miRNAs in patient samples ( n = 43) and for other reasons, such as for not having statistically significant results or wrong miRNA sequence ( n = 6). Finally, the review was performed on a total of 177 studies [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 …”
Section: Resultsmentioning
confidence: 99%